Proximal analysis of male mangrove crab, Ucides occidentalis (Ortmann, 1897) and value-added alternatives, Ecuador - Zambrano, René (2025)
The mangrove crab Ucides occidentalis (Ortmann, 1897) is a fishery resource in Ecuador regulated only for catching males, which are commercialized mainly in packages of 12 individuals. Our objective was to analyze the meat crab of U. occidentalis cooked by two methods (boiling and steaming) as well as show two alternatives of added value (nuggets: aromatic and coconut). Crabs were collected from commercial catches made on Mondragon Island, Gulf of Guayaquil. The meat crab was extracted by hand and the percentages of protein, fat and ash were determined. Consumer preference was evaluated by a sensory panel. A total of 72 male crabs were processed, ranging in size from 75 to 88 mm carapace width. Proximal analysis showed similar values for both cooking methods. Steaming: 21.8% protein, 1.73% fat, 7.24 ash, and boiling: 22.20% protein, 1.95% fat, 6.74% ash. The participants rated the crab nuggets as "good". The aromatic nugget was better than the coconut nugget. Our proximal analysis of male U. occidentalis showed values higher than previously reported for the Gulf of Guayaquil (13.38% protein, 0.45% fat, 2.49% ash), but close to those reported for other crab species (16.5-24.38% protein, 0.5-2.09% fat, and 1.02-2.25% ash). It is important to consider food alternatives based on U. occidentalis and its derived products, such as chitin, proteins, related molecules (e.g., enzymes, peptides) and nanomembrane production.